Molecular Medical Microbiology: VOL.1 - Sussman, Max; Ed (Academic Press, 2002)
Written by a panel of authors who are expert in their respective disciplines, this book includes information on vaccine development, molecular technology and diagnostic technology. It provides developments in both molecular and clinical research.